2013
DOI: 10.5194/acp-13-1999-2013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling a typical winter-time dust event over the Arabian Peninsula and the Red Sea

Abstract: Abstract. We used WRF-Chem, a regional meteorological model coupled with an aerosol-chemistry component, to simulate various aspects of the dust phenomena over the Arabian Peninsula and Red Sea during a typical winter-time dust event that occurred in January 2009. The model predicted that the total amount of emitted dust was 18.3 Tg for the entire dust outburst period and that the two maximum daily rates were ~2.4 Tg day−1 and ~1.5 Tg day−1, corresponding to two periods with the highest aerosol optical depth t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
85
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 69 publications
(74 reference statements)
15
85
1
Order By: Relevance
“…The stations close to the Red Sea had a high number of dust observations during summer and autumn, consistent with the results of Jiang et al (2009); Kalenderski et al (2013) and Klingmüller et al (2016).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The stations close to the Red Sea had a high number of dust observations during summer and autumn, consistent with the results of Jiang et al (2009); Kalenderski et al (2013) and Klingmüller et al (2016).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, the first modelling study, Miller and Tegen (1998), who examined the effect of dust on radiation, showed that dust aerosols reduce the global average surface radiation by 3 Wm −1 during summer in the northern hemisphere. Balkanski et al (2007) evaluated the annual decrease in global surface net radiation in the range from −1.11 to 0.92 Wm −1 , and this value increased by two orders of magnitude to 2.3 Wm −1 (Kalenderski et al, 2013). In contrast, Jish Prakash et al (2015) simulated the dust event on 18-22 March 2012 and found that most of the dust over the western Arabian Peninsula was deposited in the Red Sea, reaching a maximum of 0.23 Mt day −1 with 1.2 Mt deposited during the event.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the proportionality constant, c (Eq. 1), of the AFWA simulation was set to a value, representative for the Arabian Peninsula, of 0.4 as suggested by Kalenderski et al (2013). Studies have shown that c can range from 0.4 to 0.65 (Zhao et al 2010;Su and Fung 2015) to accommodate various regions of the world.…”
Section: Ambient Datamentioning
confidence: 99%
“…Prakash et al (2015) used the ''online'' meteorological and chemical transport weather research and forecasting/chemistry (WRF-Chem) model to study the effect of dust events in the Arabian Peninsula on radiation fluxes and regional climate characteristics. Using the same model, Kalenderski et al (2013) simulated a typical winter-time dust event over the Arabian Peninsula and the Red Sea and found that the total amount of emitted dust was 18.3 Tg for the entire dust outburst period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation